Sustainability Integration in Wine Destination Branding : A Comprehensive Review Perspective Fostering UN Sustainable Development Goals 2030 - Ravichandran, Sabari Shankar; Koshy, Elizabeth Renju; Mathew, Sonia Katherin (Prabandhan: Indian Journal of Management, 2023)
Purpose : This research work intended to evaluate the factors that could inculcate sustainability elements in branding wine destinations that align with the United Nations’s Sustainable Development Goals 2030. Methodology : An intensive review of literature was carried out in the contexts of wine tourism, sustainability, and destination branding. Research publications in high-quality journals were reviewed, and the perspectives were generated based on our reflections. Key Findings : The perspective highlighted wine destination image, wine destination personality, technology inclusions, stakeholders’ and destination culture, wine destination policies, and wine destination marketing communication as the key dimensions to be considered for imposing sustainability elements while branding the wine destinations. Practical Implications : The insights generated here will assist policymakers and governments in aligning wine tourism transactions with the 2030 Sustainable Development Goals of the United Nations, and they suggested profitable positioning of wine destinations with sustainability value propositions. Additionally, they pointed to areas that require further research, which were potentially the most important ones in the field of wine tourism.